The economic costs of illness in low income countries: the case of rural Ethiopia - Asfaw, Abay; von Braun, Joachim; Admassie, Assefa; Jütting, Johannes (2004)
The conventional costs of illness approach that limits the impact of illness only to direct costs (financial and time costs) is likely to underestimate the costs of illness and the potential welfare gains from different health-related policy interventions in the rural areas of developing countries. In this study, using a three round panel data and a fixed effect two-stage least squares method, we investigate both the direct and indirect costs of illness for rural households of Ethiopia. The results show that besides directly consuming a significant portion of the households' income, illness has a statistically and economically significant negative impact on the farm and non-farm income of rural households, and the results are robust irrespective of the way illness is measured. The study also reveals that the illness of any adult household member has a statistically significant negative impact on the income of the households. The results also demonstrate that improving the health status of rural households can play a significant role in poverty reduction by reducing illness inflicted time losses and increasing the productive capacity of the households.